Diet or exercise: The role of diet and/or exercise on changes of pro-inflammatory markers during a weight loss program in adult women with overweight. (August 2021) - Muhammad, Harry Freitag Luglio; Pahdarina, Diwyacitta; Zahara, Nindya Putri; Nugraheni, Fatwa; Hanny, Thalitha Almira; Ermamilia, Aviria; Huriyati, Emy
Summary: Background and aims: Obesity is associated with increased inflammation leading to a higher risk for non-communicable diseases. There was a controversy about whether exercise has a better influence on reducing inflammation during a lifestyle modification program among individuals with obesity. The objective of this study was to evaluate whether exercise could provide a benefit in reducing inflammatory markers in the context of a weight loss program. Methods: This is an experimental study with control. Subjects were pre-menopausal adult women with overweight and assigned for low-calorie diet only (LCD) or low-calorie diet and exercise (LCDex) without randomization. We compared the effect of LCDex (n = 36) and LCD (n = 36) on inflammation markers (leptin and interleukin 6/IL6) for 8 weeks. Results: We showed that after the weight loss program, there was a significant increase in IL6 (p = 0.009) but no changes in leptin (p = 0.760) concentration in both groups. There were no difference in changes of IL6 between LCDex and LCD (p = 0.483). Conclusions: A weight loss program was associated with increased inflammation. Among premenopausal women with overweight, a combination of LCD with exercise does not provide a greater benefit in reducing inflammation than those with LCD alone. Trial registration: KE/0700/06/2018. Highlights: Inflammation marker was increased at the end of weight loss program. Adding exercise did not provide a greater benefit in reducing inflammation. A combination of a low-calorie diet (LCD) with exercise provides greater weight loss than LCD only.